Islamic Values in Palang Pintu Procession in Semiotic Perspective - Iskandarsyah Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Palang Pintu tradition is a tradition that is part of the Betawi wedding ceremony. In this study, the semiotic analysis of Roland Barthes was used. This study uses extra-qualitative research methods with an interpretive approach as a compliment. This linguistic research is classified as interpretive research because it relies on interpreting texts related to the context in it, such as ideological, moral, cultural, and spiritual values. In this study, the researcher aimed to analyze the meaning of the Palang Pintu procession in terms of semiotics. From the results of the study, it can be concluded that in Palang Pintu, there are 1) meanings of denotation in the procession of the Palang Pintu, processions are starting from the dustur prayer, greetings, rhyme contests, fighting, and reciting the holy verses of the Koran or chanting sike. In the denotative meaning of this Palang Pintu process, apart from explaining the literal sense and describing the process. It also describes the stages of testing for the groom to marry his bride; 2) the connotation meaning in the Palang Pintu procession describes the practice of the teachings and laws of Islam and love for the Prophet Muhammad SAW and family ties; and 3) the myth in the Palang Pintu procession is that there are Betawi solid community principles, namely recitation, prayer, and silat. In addition, the dominance of solid Islamic teachings is evidenced by the existence of relevant verses of the Koran and hadith and the content of Betawi cultures, such as rhyming, where rhymes are used to advise on traditional art ceremonies.